MINAT DAN MOTIVASI SISWA TERHADAP KEGIATAN EKSTRAKURIKULER SEPAKTAKRAW DI SD NEGERI 2 JUNGSEMI (Indonesian Journal for Physical Education and Sport, 2021)
The focus of this research is to find out the interest and motivation for the extracurricular of sepaktakraw. This research approach uses quantitative descriptive with test survey method. The population is all students who take extracurricular activities at SD Negeri 2 Jungsemi. The sample use was a purposive sampling technique, namely students who took part in sepaktakraw extracurricular activities totaling 25 students. The results of the study were on the variable of interest in categories. Which shows three indicator of 48%, namely feelings of preasure, student interest, and students involvement. Indicator of student attetion is 56%. While the intrinsic and extrinsic motivation variable in the high category are 48%. Based on the results of research on students who take part in sepaktakraw extracurricular activities at SD Negeri 2 Jungsemi it can be said the all student interests are in the medium category and student motivation is in the high category.